CCN5 Reduces Ligamentum Flavum Hypertrophy by Modulating the TGF‐β Pathway. Issue 12 (1st August 2019) - Ye, Sunghyeok; Kwon, Woo‐Keun; Bae, Taegeun; Kim, Sunghyun; Lee, Jang‐Bo; Cho, Tai‐Hyoung; Park, Jung‐Yul; Kim, Kyoungmi; Hur, Junho K.; Hur, Junseok W.
ABSTRACT: Ligamentum flavum hypertrophy (LFH) is the most important component of lumbar spinal canal stenosis. Although the pathophysiology of LFH has been extensively studied, no method has been proposed to prevent or treat it. Since the transforming growth factor‐β (TGF‐β) pathway is known to be critical in LFH pathology, we investigated whether LFH could be prevented by blocking or modulating the TGF‐β mechanism. Human LF cells were used for the experiments. First, we created TGF‐β receptor 1 (TGFBR1) knock out (KO) cells with CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 biotechnology and treated them with TGF‐β1 to determine the effects of blocking the TGF‐β pathway. Subsequently, we studied the effect of CCN5, which has recently been proposed to modulate the TGF‐β pathway. To assess the predisposition toward fibrosis, α‐smooth muscle actin (αSMA), fibronectin, collagen‐1, collagen‐3, and CCN2 were evaluated with quantitative real‐time polymerase chain reaction, western blotting, and immunocytochemistry. The TGFBR1 KO LF cells were successfully constructed with high KO efficiency. In wild‐type (WT) cells, treatment with TGF‐β1 resulted in the overexpression of the messenger RNA (mRNA) of fibrosis‐related factors. However, in KO cells, the responses to TGF‐β1 stimulation were significantly lower. In addition, CCN5 and TGF‐β1 co‐treatment caused a notable reduction in mRNA expression levels compared with TGF‐β1 stimulation only. The αSMA protein expression increased with TGF‐β1 but decreased with CCN5 treatment. TGF‐β1 induced LF cell transdifferentiation from fibroblasts to myofibroblasts. However, this cell transition dramatically decreased in the presence of CCN5. In conclusion, CCN5 could prevent LFH by modulating the TGF‐β pathway. © 2019 The Authors. Journal of Orthopaedic Research ® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 37:2634–2644, 2019